THE EFFECT OF USING PLOTAGON APPLICATION INTO STUDENTS’ SPEAKING SKILL FOR SEVENTH GRADE AT SMP METHODIST TANJUNG MORAWA - Richad Hamonangan; Erika Sinambela; Sondang Manik (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2024)
Plotagon is a multifunctional animation application that helps students to create their own stories in various languages ​​through texting or recording our voices. The use of animation for education is very important because animation can help students to solve problems that they encounter in the subject matter by making students imagine the subject matter. This research explores the effectiveness of the Plotagon application in enhancing the speaking skills of seventh-grade students at SMP Methodist Tanjung Morawa. In this research, the researcher will collect data by experimenting. The experimental research describes what happened with particular variables where there is certain treatment given to the students, so that this study uses an experimental study as one form of quantitative research to see the effectiveness of using Plotagon application into students’ speaking skill of the 7th grade students of SMP Methodist Tanjung Morawa. A control group received conventional instruction, while the experimental group was taught using Plotagon. The findings indicate that students in the experimental group showed significant improvement in their speaking skills, demonstrating increased motivation, engagement, and confidence. The results suggest that integrating animation-based applications like Plotagon into English language learning can enhance students' speaking proficiency and overall language acquisition.